2018
DOI: 10.1016/j.polymdegradstab.2018.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Early-stage photodegradation of aromatic poly(urethane-urea) elastomers

Abstract: 16The photooxidative stability of an aromatic segmented poly(urethane-urea) (PUU) elastomer, 17 stabilised with a range of carbon black fillers, was assessed after very low UVA doses as a means to 18 identify components that are highly susceptible to UV degradation, and suggest better design of such 19 materials. Fourier-transform infrared (FTIR) analysis indicated rapid degradation of the urea bonds 20 in the hard segments, followed by chain scission and photo-Fries reaction of the urethane linkages. In 21 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This result is in partial agreement with the literature, 32,33,58 as other studies have reported a decreasing 1597 cm −1 band, attributing it to CC stretching vibrations in aromatic rings. 29,59 Other notable changes in the irradiated samples were the increasing carbonyl peak at 1704 cm −1 wavenumber in all PU microplastics (Fig. S7.8†), a strong indicator of photo-oxidation; 9,19,49 the increasing and broadening 3200–3600 cm −1 wavenumber region in all PU microplastics (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This result is in partial agreement with the literature, 32,33,58 as other studies have reported a decreasing 1597 cm −1 band, attributing it to CC stretching vibrations in aromatic rings. 29,59 Other notable changes in the irradiated samples were the increasing carbonyl peak at 1704 cm −1 wavenumber in all PU microplastics (Fig. S7.8†), a strong indicator of photo-oxidation; 9,19,49 the increasing and broadening 3200–3600 cm −1 wavenumber region in all PU microplastics (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…† Overall, the results of the ATR-FTIR analysis aligned well with the scientic literature. 29,32,33,35,36,[57][58][59] For all PU microplastics, yellowing via the quinonoid route was supported by the emergence of a band at 814 cm −1 (out-of-plane C-H bending vibration in 1,4-disubstituted aromatic rings) that had decreased by receiving a UV dose of 350 MJ m −2 , indicating that aromatic rings were degraded (Fig. S7.6 †).…”
Section: Total Organic Carbonmentioning
confidence: 95%
“…Moreover, upon soaking in 40% H 2 SO 4 aqueous solution, the peak intensity of the stretching vibration peak of C–O–C at 1104 cm −1 decreased, inferring that the hydrogen on the α-carbon atom of the PTMEG ether bond may be oxidized by an acid. 52,53 More severe decomposition of the chemical bonds of the elastomer led to the deterioration in the strength of XDI-PUE after soaking in an acid. Therefore, it is believed that the present PUE is more suitable for use under alkali conditions.…”
Section: Resultsmentioning
confidence: 99%
“…direct photolysis of C−C and C−H bonds, the presence of residue from the catalyst used in polymerization, Norrish-I and Norrish-II type reactions due to the presence of a carbonyl group, the attack of oxygen on C−C/C=C bond, the presence of hydroperoxide and/or the photo-Fries reaction which leads to the formation of free radicals. 21 In general, UV radiation in ambient sunlight has wavelength in the range of 290 nm–400 nm. Therefore, the polymer degradation due to ambient sunlight exposure is primarily driven by the UV radiation.…”
Section: Introductionmentioning
confidence: 99%